PENGARUH BEA BALIK NAMAKENDARAAN BERMOTOR KOTA KEDIRI TERHADAP PENDAPATAN ASLI DAERAH PROVINSI JAWA TIMUR - Vida Windita Putri; Subagyo Subagyo; Wibowo Andoko (CAHAYA AKTIVA, 2018)
The increasing number of residents in the city of Kediri, it is assumed or considered the number of needs for motor vehicles will increase. With the increase in the number of motor vehicles, it can be considered that the amount of Transfer Fee of Motor Vehicle of Kediri will increase. Based on these studies the authors are interested in conducting research on the Effect of Title Behavior of Motor Vehicles of Kediri on Local Revenue East Java Province. Based on the research, the purpose of this research is to know the development and influence of title transfer of motor vehicle of Kediri City and East Java Province Original Revenue. This research was conducted at the East Java Regional Revenue Service and Technical Implementation Unit of East Java Province Revenue Service. Sources of data in this study using secondary data and using the type of quantitative research with data collection methods used are literature study and documentation. While the method of data analysis using descriptive statistical analysis and statistical analysis. Based on the result of this research, it can be concluded that the development of Transfer of Motor Vehicle Title Tendency tends to be unstable even though the development of East Java Provincial Revenue tends to increase, while the influence of Transfer of Motor Vehicle Title to Regional Revenue of East Java Province is not significant. It is advisable that the government, particularly the Implementation Unit of the East Java Province Revenue Service, should pay more attention to the transfer of ownership of motor vehicles from each taxpayer in order to increase the revenues of Vehicle Transfer of Title of the Kediri Motor Vehicle so that the increase of revenue can increase income in the Province. Keywords: Development, Receipts, Income, Influence of Transfer of Motor Vehicle Title Fee.